Investment appraisal in developing countries - Amachree, Sokeiprim M. O. (Aldershot, Hants, England ; Brookfield, Vt., USA : Avebury, 1988)
The aim of this book is to develop a suitable appraisal technique for the industrial investment proposals in Less Developed Countries.
Includes bibliographies.
osc 10/5/17
Loans
Keywords: Industrial Development Projects; Capital Investments; Input-Output Analysis